Designing a Compensation System Model with a Social Justice Approach in the National Iranian Oil Company - Nozari, Moslem; Amirnejad, Ghanbar; Taheri Goodarzi, Hojjat; Derakhshan, Rostam (Future of Work and Digital Management Journal, 2025)
Social justice encompasses a set of actions and policies in various domains aimed at creating a fairer and more equitable society. The purpose of this study was to design a compensation system model with a social justice approach in the National Iranian Oil Company. This research was applied in nature and employed a mixed-methods design, combining both quantitative and qualitative approaches. Considering the research objective, the layered research model of Saunders et al. (2016) was used to explain the layers of research from philosophy to technique. An inductive approach was adopted, and based on inductive reasoning from the insights obtained, the relevant model was developed. In this process, the use of informed experts as well as adherence to scientific methodology was also applied. Data were collected through semi-structured interviews and content analysis of texts. In addition to face validity, convergent validity and construct validity were employed, the results of which confirmed the validity. The target statistical population included 20 experts, professors, specialists, and senior managers of the National Iranian Oil Company. Descriptive and inferential statistics were used for the interview averages with SPSS software, and confirmatory factor analysis was conducted using LISREL software. The findings led to the design of a model in which social justice is grounded on certain pillars that contribute to the compliance and reinforcement of the compensation system in organizations. These pillars included fair laws, just and virtuous implementers, supervision, and public awareness.